2021
DOI: 10.3390/biomedicines9101437
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction in the Cystic Fibrosis Transmembrane Regulator in Chronic Obstructive Pulmonary Disease as a Potential Target for Personalised Medicine

Abstract: In recent years, numerous pathways were explored in the pathogenesis of COPD in the quest for new potential therapeutic targets for more personalised medical care. In this context, the study of the cystic fibrosis transmembrane conductance regulator (CFTR) began to gain importance, especially since the advent of the new CFTR modulators which had the potential to correct this protein’s dysfunction in COPD. The CFTR is an ion transporter that regulates the hydration and viscosity of mucous secretions in the airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…Frequent exacerbator LABA, LAMA, ICS, roflumilast, macrolides Optimisation of comorbid physical and mental health conditions [27] Chronic bronchitis Roflumilast, mucolytics Use of CFTR modulators [13] Emphysema Lung volume reduction surgery Correction of miR overexpression [8] Type 1 respiratory failure Long-term oxygen therapy Increased vigilance for VTE in acute illness [29] Type 2 respiratory failure Domiciliary NIV Consideration of comorbidities such as OSA/ORRF [21] Eosinophilic COPD Steroids Identification of distinct microbiome in eosinophil-predominant COPD [15] Investigation of immunomodulatory alternatives to steroids [30] Bronchiectasis Targeted antibiotics, chest physiotherapy Identify severity clusters using biomarkers, to stratify follow-up and hospitalisation [33] α-1 antitrypsin deficiency LABA, LAMA, ICS α-1 antitrypsin augmentation therapy [17] Subgroups requiring further study Biomass and pollutant COPD Removal of pollutant exposure Use of predictive machine-learning to target individuals at greatest risk of pollutant-induced emphysema [31] Premalignant COPD Smoking cessation…”
Section: Subgroup Established Treatment Future Management Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequent exacerbator LABA, LAMA, ICS, roflumilast, macrolides Optimisation of comorbid physical and mental health conditions [27] Chronic bronchitis Roflumilast, mucolytics Use of CFTR modulators [13] Emphysema Lung volume reduction surgery Correction of miR overexpression [8] Type 1 respiratory failure Long-term oxygen therapy Increased vigilance for VTE in acute illness [29] Type 2 respiratory failure Domiciliary NIV Consideration of comorbidities such as OSA/ORRF [21] Eosinophilic COPD Steroids Identification of distinct microbiome in eosinophil-predominant COPD [15] Investigation of immunomodulatory alternatives to steroids [30] Bronchiectasis Targeted antibiotics, chest physiotherapy Identify severity clusters using biomarkers, to stratify follow-up and hospitalisation [33] α-1 antitrypsin deficiency LABA, LAMA, ICS α-1 antitrypsin augmentation therapy [17] Subgroups requiring further study Biomass and pollutant COPD Removal of pollutant exposure Use of predictive machine-learning to target individuals at greatest risk of pollutant-induced emphysema [31] Premalignant COPD Smoking cessation…”
Section: Subgroup Established Treatment Future Management Considerationsmentioning
confidence: 99%
“…Finally, although we are aware of inflammatory and immune-mediated pathways in COPD pathogenesis, we are unclear regarding which factors determine whether patients exposed to tobacco will develop the condition. An included review by Carrasco-Hernández et al outlines the tobacco-associated functional alteration of the cystic fibrosis transmembrane conductance regulator (CFTR) in COPD, resulting in airway dehydration [ 13 ]. They describe fascinating research methods that have been applied to COPD, such as using CFTR-deficient mice to build models of smoke-induced COPD.…”
Section: Phenotype-guided Therapiesmentioning
confidence: 99%
“…CFTR gene is located on chromosome 7, and mutations of this gene decrease the availability of the functional CFTR ion channel protein, which belongs to the ATP-binding cassette (ABC) family of proteins with transmembrane transport functions (Rommens et al, 1989). These genetic mutations elicit the synthesis of a dysfunctional CFTR protein associated primarily with a disruption in normal chloride (Cl − ) and bicarbonate (HCO 3 − ) ion transport (Anderson et al, 1991;Saint-Criq and Gray, 2017), which causes a lack of hydration in the extracellular mucus and secretions (Carrasco-Hernández et al, 2021). The functional impairment of mutated CFTR protein particularly affects the gastrointestinal and respiratory systems; however, other systems and organs are significantly involved (O'Sullivan and Freedman, 2009;Elborn, 2016).…”
Section: Introduction 1cystic Fibrosis: From Disease To Molecular Alt...mentioning
confidence: 99%
“…Bacterial colonization and inflammation are potential drivers of airway obstruction, airway destruction, remodeling, and exacerbations. [1][2][3][4] Icenticaftor was found to be safe and well tolerated both in healthy volunteers and patients with cystic fibrosis and demonstrated clinically meaningful changes in lung function in 16 patients with cystic fibrosis at 450 mg given twice daily for 14 days. 5 Following this positive finding, icenticaftor in a randomized double-blind placebo-controlled study showed an improvement of change in forced expiratory volume in 64 patients with COPD versus 28 placebo patients with COPD when dosed with 300 mg twice daily for 28 days.…”
mentioning
confidence: 98%
“…Based on its mechanism of action, icenticaftor is expected to provide benefits in patients with chronic obstructive pulmonary disease (COPD) by restoring mucociliary clearance, which would eventually lead to a reduction of bacterial colonization and related inflammatory cascade. Bacterial colonization and inflammation are potential drivers of airway obstruction, airway destruction, remodeling, and exacerbations 1–4 . Icenticaftor was found to be safe and well tolerated both in healthy volunteers and patients with cystic fibrosis and demonstrated clinically meaningful changes in lung function in 16 patients with cystic fibrosis at 450 mg given twice daily for 14 days 5 .…”
mentioning
confidence: 99%